Graphene Nanoplatelets Render Poly(3-Hydroxybutyrate) a Suitable Scaffold to Promote Neuronal Network Development - Moschetta, Matteo; Chiacchiaretta, Martina; Cesca, Fabrizia; Roy, Ipsita; Athanassiou, Athanassia; Benfenati, Fabio; Papadopoulou, Evie L.; Bramini, Mattia (Frontiers in Neuroscience, 2021)
The use of composite biomaterials as innovative bio-friendly neuronal interfaces has been poorly developed so far. Smart strategies to target neuro-pathologies are currently exploiting the mixed and complementary characteristics of composite materials to better design future neural interfaces. Here we present a polymer-based scaffold that has been rendered suitable for primary neurons by embedding graphene nanoplatelets (GnP). In particular, the growth, network formation, and functionality of primary neurons on poly(3-hydroxybutyrate) [P(3HB)] polymer supports functionalized with various concentrations of GnP were explored. After growing primary cortical neurons onto the supports for 14 days, all specimens were found to be biocompatible, revealing physiological growth and maturation of the neuronal network. When network functionality was investigated by whole patch-clamp measurements, pure P(3HB) led to changes in the action potential waveform and reduction in firing frequency, resulting in decreased neuronal excitability. However, the addition of GnP to the polymer matrix restored the electrophysiological parameters to physiological values. Interestingly, a low concentration of graphene was able to promote firing activity at a low level of injected current. The results indicate that the P(3HB)/GnP composites show great potential for electrical interfacing with primary neurons to eventually target central nervous system disorders.